The Role Of Product Quality, Quality Of Human Resources, And Corporate Culture In Improving Company Performance Through Business Strategy - Wibowo, Bagus Yunianto; Ade, Sinar Hubtrian; Nurhidayah, Evinta Amalia (LP2M IAIN Palopo, 2024)
This study aims to analyze of product quality, human resource (HR) quality, and company culture on business strategy. As well as the influence of product quality, quality of HR, corporate culture, and business strategy at company performance. The population in this study is the manager of micro units for the 2021-2022 period which amounted to 147 with a sample using a population of 147 respondents and the data processed amounted to 102 respondents. Analyzer using SEM (structure equations modeling) The results of investigation prove that product quality has a sign on business strategy. HR quality has a sign on business strategy. Corporate culture does not affect business strategy. The quality of the product does not affect the performance of the enterprise. The HR quality does not affect company performance. Corporate culture has a sign effect in company performance and business strategy has a sign effect on company performance